Trends of transfusion transmissible diseases among blood donors at Uttarakhand, India - Gita Negi; Dushyant Singh Gaur (Wolters Kluwer Medknow Publications, 2014)
Context: Blood can save lives; however, it can be a source of transfusion transmitted diseases if proper screening of donated blood is not done. It is now mandatory to screen all donated blood units, whether replacement or voluntary for five transfusion transmitted diseases-namely human immunodeficiency virus (HIV), hepatitis B and C, syphilis, and malaria. Aims: The present study was done to study the prevalence of infectious disease markers among donors at the blood bank of a tertiary care center. Settings and Design: A total of 53,069 donors donated blood over 11 years. The number of replacement and voluntary donors was 41,710 and 11,359, respectively. Materials and Methods: Screening of blood units was done by enzyme-linked immunosorbent assay (ELISA) method for HIV and hepatitis B and C. HIV testing was done using fourth generation ELISA kits. Syphilis was tested by latex agglutination assay and malaria was tested using slide method up to the year 2008-2009 and by rapid immunochromatographic assay after that. Results: The mean percentage of these infections per year was found to be 0.2, 1.2, 0.9, 0.3, and 0.002% for HIV, hepatitis B surface antigen (HBsAg), hepatitis C virus (HCV), syphilis, and malarial parasite (MP), respectively. Conclusions: The risk of transfusion transmissible infection (TTI) today is low but supply of safe blood depends on proper donor selection and sensitive screening tests.